The short-run impact of interest rates on exchange rates: Results for the Swiss franc against the euro and US dollar from daily data 2001-2011 - Peter Kugler (University of Basel, Center of Business and Economics (WWZ), 2020)
This paper provides an econometric analysis of the short-run impact of interest rates on the Swiss franc exchange rate covering the period January 2001 to June 2011 using daily data. Our model includes both the exchange rate of the Swiss franc against euro and dollar and uses the plausible assumption that foreign interest rates and the euro-dollar exchange rate are exogenous. In addition, we consider not only money market interest differentials, but also those for 2 and 10 year governments bonds. GMM estimation indicates that a one-percentage point increase in the 3-month Swiss franc Libor rate leads to a 3.7 % appreciation of the Swiss franc against euro and dollar. This result seems to be robust with respect to considering only increasing or decreasing interest rates and omitting data around SNB target band adjustments. Our findings appear reasonable and are between the extremely low and high estimates of the impact of Swiss interest rate changes on the exchange rate reported in the literature.
Keywords: 330; Wechselkurs; Zins; Zinsparität; Schweizer Franken; US-Dollar; Euro; Schweiz